Relationship between per capita births of Cook Inlet belugas and summer salmon runs: age‐structured population modeling. Issue 1 (2nd January 2020) - Norman, Stephanie A.; Hobbs, Roderick C.; Beckett, Laurel A.; Trumble, Stephen J.; Smith, Woutrina A.
Abstract: Anthropogenic disturbances may alter a population's conservation status if the ability of individuals to survive and breed is affected. We used an adaptation of the Heligman‐Pollard model to estimate survival at age of Cook Inlet belugas (CIB; Delphinapterus leucas ), an endangered population in south‐central Alaska. We developed an age‐structured Leslie matrix model, based on the life history parameters survival and fecundity probability, to evaluate the sensitivity of population size and growth of CIB, to variation in estimate values of Chinook and coho salmon abundance in the Deshka River, a major tributary of the Susitna River. Birth effect ( e b ) was regressed against Chinook and coho salmon levels for the year of, the year before, and two years before a beluga calf birth. The effect of a range of modifications of salmon availability was illustrated in CIB with a series of simulations. The maximum annual population growths (λ) were set at 1.036 (3.6%). Ranges of CIB survival and fecundity probabilities indicated small changes in survival probabilities have a greater impact on population growth than similar changes in birth probability. As either survival ( e s ) or fecundity ( e b ) was reduced, the annual growth declined, with either e s = 0.961 or e b = 0.388, causing a decreased annual growth of −0.4%. Regressions of Chinook salmon for the year of, the year before, and two years before a birth were all significant at the 5% level as was coho in the year of and year prior to birth. The mechanism model with the best fit was the sum of Chinook and coho in the year of birth and year prior to birth. Simulations showed that if salmon runs remained at their current levels, the CIB population would likely continue its current slow decline and per capita births would continue to be low. The results from this study suggest reproductive success in CIB is tied to salmon abundance in the Deshka River. Current management practices should consider this when setting research priorities, designing new studies, and developing management actions to achieve CIB population recovery targets.